Evaluation of the green development efficiency of marine fish culture in China - Sun, Longqi; Yang, Zhengyong; Wang, Qiang; Peng, Lewei; Zhang, Zhiyi; Liu, Dong; Li, Simin (Frontiers in Sustainable Food Systems, 2023)
Green development efficiency (GDE) is an important criterion for measuring the level of green development. It considers not only economic development efficiency but also environmental costs. In China, marine fish culture, as one of the pillar industries of mariculture, is promoting green development and industrial transformation and upgradation. Based on data from field surveys of marine fish farmers (2017-2019) and the China Fishery Statistical Yearbook (2018-2020), this paper establishes an evaluation index system and uses the superslack-based measure model (Super-SBM) to evaluate the GDE of marine fish culture. The results show that the average GDE of marine fish culture in China was 0.9529, which was in an inefficient state. As for culture species, golden pompano (Trachinotus ovatus) and cobia (Rachycentron canadum) were the two species farmed in an efficient state, with the GDE of 1.2107 and 1.0659, respectively. Regarding culture modes, green modes (offshore cage aquaculture, industrial recirculating aquaculture, engineering pond aquaculture) were in an efficient state, with the GDE of 1.2310, 1.0827, 1.0401, respectively. Traditional modes (industrial flow-through aquaculture, ordinary cage aquaculture, ordinary pond aquaculture)were in an inefficient state, their GDE were 0.9884, 0.8746, 0.8248, respectively. Green modes have higher GDE than traditional modes. In contrast, the production and culture areas of green modes were less than those of traditional modes, due to the profits of the same species in green modes were lower than those in traditional modes. The results of this study present an objective assessment of the GDE of marine fish culture in China and provide valuable insights for analyzing mechanisms to improve the GDE of marine fish culture.